Combine two different dengue vaccines could efficiently target dengue-naive subjects. Comment to Macias A, Ruiz-Palacios G, Ramos-Castaneda J. Combine dengue vaccines to optimize effectiveness. Vaccine. 2020 Jun 26;38(31):4801– 4804 - Guy, Bruno (Vaccine, 2021)
[...]while TAK-003 vaccine induces high protection against DENV2 and to a lesser extent against DENV1 in both dengue-seropositive and -seronegative individuals, responses and protection are dominated by DENV2 and an inconclusive relative risk > 1 has been observed for DENV3 in seronegative vaccines, while no conclusion could be drawn regarding DENV4 [2]. [...]TAK-003 could lead to potential safety problems in baseline-seronegative persons as seen for Dengvaxia®, in particular for those exposed to serotype 3. [...]TAK-003/CYD-TDV prime-boost would initially ensure strong humoral and cellular responses against anti-DENV2 - the weakest CYD-TDV serotype -, and then eventually strengthen responses against the other serotypes, in particular DENV4 - the dominant CYD-TDV and weakest TAK-003 serotype. Heterologous CYD-TDV boost of a prior DENV2-like priming would also be more likely to induce broader cross-reactive immune responses at both humoral and cellular levels, as observed upon heterologous secondary wild type infection and CYD-TDV immunization in dengue-seropositive individuals. [...]CYD-TDV possesses a YF-17D backbone, decreasing the risk of being negatively impacted by initial TAK-003-induced cellular responses directed against DENV2 non-structural antigens.